Interactive Experience in the Digital Age Evaluating New Art Practice - Candy, Linda; Ferguson, Sam (Springer Series on Cultural Computing, 2014)
The use of interactive technology in the arts has changed the audience from viewer to participant and in doing so is transforming the nature of experience. From visual and sound art to performance and gaming, the boundaries of what is possible for creation, curating, production and distribution are continually extending. As a consequence, we need to reconsider the way in which these practices are evaluated.   Interactive Experience in the Digital Age explores diverse ways of creating and evaluating interactive digital art through the eyes of the practitioners who are embedding evaluation in their creative process as a way of revealing and enhancing their practice. It draws on research methods from other disciplines such as interaction design, human-computer interaction and practice-based research, and adapts them to develop new strategies and techniques for how we reflect upon and assess value in the creation and experience of interactive art.   With contributions from artists, scientists, curators, entrepreneurs and designers engaged in the creative arts, this book is an invaluable resource for both researchers and practitioners, working in this emerging field.